Human finger input properties for precise target selection on multi-touch screen - Ahsanullah, S.S. (Institute of Electrical and Electronics Engineers Inc., 2014)
In recent years, touch enabling technologies potentially have supported to design and develop small and large sizes of multi-touch screens. These sensitive devices assist users to select and manipulate the target objects using their bare fingers. However, it is reported that user fingertips cause the imprecise selection of small size targets and subsequently users get frustrated during interaction. Keeping in view this problem, it is attempted to provide an overview on human finger input properties and their possible use for the selection of targets on multi-touch screens. This survey paper helps in understanding the finger touch input and some inherited finger input properties. It also provides a rational to explore the finger input properties that may help in proposing new interaction techniques to avoid the imprecision problem. Â© 2014 IEEE.